1995
DOI: 10.1111/j.1365-3083.1995.tb03530.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and Murine Autoimmune Encephalomyelitis: Inhibition or Enhancement of Disease with Antibodies to Select Cytokines, or by Delivery of Exogenous Cytokines Using a Recombinant Vaccinia Virus System

Abstract: To examine the complex role of cytokines in the pathogenesis of actively induced murine EAE we measured the levels of a number of cytokines (IL-6, IFN gamma and TNF) in the spinal cord and CSF of mice with active experimental autoimmune encephalomyelitis (EAE) and found them all to be elevated. We next treated mice with antibodies to these three cytokines, which were over expressed in the CNS, to determine if they would alter disease and found the following: anti-IL-6 had no significant effect on disease, anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(38 citation statements)
references
References 42 publications
1
36
1
Order By: Relevance
“…IL-6 displays dual pro-and anti-inflammatory roles, depending on its origin, amount, and presence of other cytokines. 38 In the context of EAE, results vary with those of Willenborg and colleagues 39 showing that application of exogenous IL-6 inhibited EAE, whereas Gijbels and colleagues 40 reported that administration of neutralizing antibodies to IL-6 reduced EAE. Although initially thought to be proinflammatory, 41 many studies indicate that IL-6 has prominent anti-inflammatory and immunosuppressive effects and may negatively regulate the acute phase response.…”
Section: Eae In Il-4r␣contrasting
confidence: 53%
“…IL-6 displays dual pro-and anti-inflammatory roles, depending on its origin, amount, and presence of other cytokines. 38 In the context of EAE, results vary with those of Willenborg and colleagues 39 showing that application of exogenous IL-6 inhibited EAE, whereas Gijbels and colleagues 40 reported that administration of neutralizing antibodies to IL-6 reduced EAE. Although initially thought to be proinflammatory, 41 many studies indicate that IL-6 has prominent anti-inflammatory and immunosuppressive effects and may negatively regulate the acute phase response.…”
Section: Eae In Il-4r␣contrasting
confidence: 53%
“…Gijbels et al (19) reported that treatment of anti-IL-6 antibody was protective against the development of EAE. By contrast, Willenborg et al (20) reported that anti-IL-6 therapy has no significant protective effect in EAE. Therefore, the role of IL-6 in EAE remains unclear.…”
Section: Il-6 Blockade By Treatment With An Anti-il-6 Receptor Monoclmentioning
confidence: 95%
“…19 There is only one report dealing with the therapeutic efficacy of systemic injection of viral vectors engineered with cytokine genes in mice affected by EAE. 28 Viral vectors derived from the WR strain of vaccinia virus (VV) and engineered to produce IL-6, TNF␣, IL-1␤, IL-2, IL-10, IL-4 or IFN␥ were intravenously injected, at the time of immunization and 6 days later, in SJL/J or (SJL/J × BALB/C)F1 hybrid mice affected by syngeneic spinal cord homogenate-induced EAE. A disease ameliorating effect was observed in EAE mice when the IL-6, TNF␣, IL-1␤, IL-2, IL-10 but not IL-4 or IFN␥ gene-containing vectors were used.…”
Section: Cytokine Gene Therapy In Experimental Autoimmune Encephalomymentioning
confidence: 99%